Performance evaluation of PV penetration at different locations in a LV distribution network connected with an off-load tap changing transformer - Dilini Almeida; Jagadeesh Pasupuleti; Janaka Ekanayake (Institute of Advanced Engineering and Science, 2021)
Solar photovoltaic (PV) power generation has shown a worldwide remarkable growth in recent years. In order to achieve the increasing energy demand, a large number of residential PV units are connected to the low voltage (LV) distribution networks. However, high integration of solar PV could cause negative impacts on distribution grids leading to violations of limits and standards. The voltage rise has been recognized as one of the major implications of increased PV integration, which could significantly restrict the capacity of the distribution network to support higher PV penetration levels. This study addresses the performance of the off-load tap changing transformer under high solar PV penetration and a detailed analysis has been carried out to examine the maximum allowable PV penetration at discrete tap positions of the transformer. The maximum PV penetration has been determined by ensuring that all nodal voltages adhere to grid voltage statutory limits. The simulation results demonstrate that the first two tap positions could be adopted to control the grid voltage under higher PV penetrations thus facilitating further PV influx into the existing network.